Integration of Industry 4.0 for a Smart and Sustainable Future of the Healthcare Sector in the Post-COVID Era - Ratri Parida; Aarti Singh; Rambabu Lavuri (Universitas Pasundan, 2021)
The COVID-19 pandemic has result in unprecedented challenges for the manufacturing and service sectors. Further, it has also tremendously affected the global healthcare sector, which is seen in the surge of demand in personal protective equipment, ventilators, masks, medicines, etc. Furthermore, according to Menear (2020), the world population is projected to be at least 8.5 billion people by 2050, including a much higher elderly population. This calls for an urgent, critical evaluation and upgrade of the healthcare sector. In this regard, an implementation of Industry 4.0 (I4.0) technologies is proposed to fulfill the sector’s current and future needs. A detailed and systematic review has been conducted using PRISMA, which highlights the various I4.0 technologies for the early detection, control, and management of the healthcare supply chain. Finally, it is imperative that I4.0 be properly implemented for better management of the global healthcare sector. The study also highlights policy implications for stakeholders.